2010
DOI: 10.1007/s11250-010-9696-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various levels of dietary Jatropha curcas seed meal on rabbits infested by the adult ticks of Hyalomma marginatum marginatum I. Animal performance, anti-tick feeding and haemogram

Abstract: The goal of this study was to investigate the use of Jatropha curcas seed meal (JCSM) in different levels as acaricide in diet of rabbits experimentally infested by Hyalomma marginatum marginatum then determining animal performance, anti-tick feeding and its effects on haemogram of rabbits. Thirty healthy mixed-breed rabbits were randomly divided into five equal groups. The first group was kept as a control fed soya bean meal (20%) as a source of protein. Groups from the second to the fifth fed diets contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…But TDM and DCP in G3 markedly increased than in G2. The increasing intakes of TDN and DCP for both G2 fed R2 and G3 fed R3 may be due to increasing in all nutrients digestibility as CP, amino acids, vitamins and minerals (Abd El-Rahman, 2008;Abdel-Shafy et al, 2011;Abd El-Rahman et al, 2011).…”
Section: Biochemical Findingsmentioning
confidence: 99%
“…But TDM and DCP in G3 markedly increased than in G2. The increasing intakes of TDN and DCP for both G2 fed R2 and G3 fed R3 may be due to increasing in all nutrients digestibility as CP, amino acids, vitamins and minerals (Abd El-Rahman, 2008;Abdel-Shafy et al, 2011;Abd El-Rahman et al, 2011).…”
Section: Biochemical Findingsmentioning
confidence: 99%
“…The seed cake can be a protein source for livestock after inactivation of trypsin inhibitors and lectins by heat treatment or defatted for the removal of the phorbol esters. Through laboratory analysis, J. curcas seed meal free of shells has been found to have high nutritive value comparable to that of soybean meal because it is rich in protein (27 to 33%) (Makkar et al, 1998;Abou-Arab and Abu-Salem, 2010;Abdel-Shafy et al, 2011). Nasr et al (2011) indicated that the administering of Jatropha seed meal (JSM) at 2.5% normal diet was not toxic in rabbits, while 5 or 7.5% JSM exhibited slight adverse sero-biochemical and histopathological alteration; although 10% JSM exhibited some sero-biochemical and histopathological alteration in liver and kidney functions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Lihua et al [ 12 ] showed that the leaf extract of the Jatropha curcas plant possesses an in vitro antibiotic effect on chicken pathogens, such as Escherichia coli . Moreover, a recent study has shown the anti-tick activity of Jatropha meal in rabbits [ 13 , 14 ].…”
Section: Jatropha Meal a Biofeed And Its Productionmentioning
confidence: 99%